Exploring the killer domains to create new value: A Comparative case study of Canadian and Korean telcos - Chulmin Lim; Joe Rowsell; Seongcheol Kim (International Telecommunications Society (ITS), 2023)
Diversifying business portfolios and creating new value has been considered essential strategy for telcos to survive and grow. In this sense, telcos need to find a promising industry called killer domains and concentrate on these to reduce the risk of business diversification. However, few studies have tried to develop criteria for identifying the killer domains applicable to a diverse industrial environment. Therefore, this study aims to explore the killer domains for Canadian and Korean telcos by developing comprehensive evaluation criteria. This study adopted the analytic hierarchy process (AHP) method and surveyed 23 telecommunication experts in Canada and 22 in Korea. From the data analysis, this study found that expected benefit is the most important criterion in decision-making for a telco's business diversification, followed by resource fit and the expected cost. In addition, there were no significant differences in the relative importance of alternative domains in Korea. However, in Canada, digital healthcare was the most crucial domain for Canadian telcos, followed by the security and immersive content industry. The result of this study provides implications for practitioners' and policymakers' decision-making regarding business diversification strategies in the telecommunication industry.
Keywords: 330; Telecommunication industry; Diversification strategy; Killer domain; Analytic hierarchy process (AHP); Canada; Korea; Comparative study